Organ Donation and the Ars Moriendi. (November 2019) - Doran, Stephen
Organ donation is rightly understood as a gift that is a genuine act of love. Organ donation as an act of love requires it to be an act of freedom that honors the integrity of the human person who is in the process of dying. However, the process of organ donation, by necessity, inserts a third party of interest whose primary aim is to assist someone other than the dying person. Caregivers can become "organ focused" instead of "patient focused." The procurement of organs potentially results in the commodification of the potential organ donor. Furthermore, death is not a momentary event but rather an ontological change in the person where the union of body and soul becomes divided. This Catholic understanding of death is important to assess the impact of organ donation on the process of dying. Family members of organ donors often have traumatic memories associated with the organ donation process, potentially overshadowing the ars moriendi —the art of dying. Summary: While organ donation is an act of love, the donation process can be distraction from the care of the dying patient, who may be treated differently than other dying patients who are not organ donors. A Catholic understanding of death is helpful in assessing the impact of the organ donation process.